2020
DOI: 10.1111/pce.13933
|View full text |Cite
|
Sign up to set email alerts
|

Wheat morpho‐physiological traits and radiation use efficiency under interactive effects of warming and tillage management

Abstract: Understanding the interactive effects of different warming levels and tillage managements on crop morphological and physiological traits and radiation use efficiency (RUE) is essential for breeding climate‐resilient cultivars. Here, we conducted temperature free‐air controlled enhancement (T‐FACE) experiments on winter wheat during two growth seasons in the North China Plain. The experiments consisted of three warming treatments and two tillage treatments (CT: conventional tillage and NT: no‐tillage). In the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…The next quantum leap in yield will be driven by optimization of the source/sink ratio, which is associated with RUE (Bustos et al., 2013; Li et al., 2021; Miralles & Slafer, 2007). In turn, a higher RUE will increase the total amount of assimilates available for spike growth and to increase the number of grains and TGW (Lynch et al., 2017; Rivera‐Amado et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The next quantum leap in yield will be driven by optimization of the source/sink ratio, which is associated with RUE (Bustos et al., 2013; Li et al., 2021; Miralles & Slafer, 2007). In turn, a higher RUE will increase the total amount of assimilates available for spike growth and to increase the number of grains and TGW (Lynch et al., 2017; Rivera‐Amado et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During the reproductive stage, the flag leaf is the most significant source organ for synthesis and production, and it is also essential for regulating final plant development and yield formation in cereal crops (Biswal & Kohli, 2013; Tian et al., 2015). Light intercepted by the canopy is another important factor for estimating RUE, which is determined by LAI and the light extinction coefficient (Furbank et al., 2019; Li et al., 2021). Our findings suggest that LAI plays an essential role in RUE (Figure 4a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Every year, breeders work hard to create cultivars that are better adapted to changing climates. The ongoing research work on wheat LTS tolerance mechanism needs to be combined with modern breeding techniques (i.e., fast breeding, space breeding, and CRISPR-Cas9) for the development of efficient and temperature resilient crop varieties (Hristov et al, 2007;Zhao et al, 2020;Li et al, 2021). For efficient utilization of P, more research is needed into the genetic and molecular mechanisms related to LTS.…”
Section: Utilizing Modern Breeding Techniques and Tools For Developin...mentioning
confidence: 99%
“…A full understanding of high temperature effects will require knowledge of how these will interact with other factors. For example, Y. Li, Hou, and Tao (2021) report that production practices such as tillage influence morphological responses during warmer seasons by negatively impacting photosynthetic parameters. L. Li et al (2021) found some influence of drought on high temperature responses and also compensation between above ground and below ground biomass on the ability of the ecosystem under study to act as a CO 2 sink, based on a four‐year field experiment.…”
Section: Carbon Dynamics As a Key Regulator Of Plant Heat Stress Responsesmentioning
confidence: 99%